El sacrificio humano: víctimas en el monte Liceo - Cardete del Olmo, Mª Cruz ('Ilu. Revista de Ciencias de las Religiones, 2006)
The human sacrifice is a very frequent image in Ancient Religions, concretely in the Ancient Greek Religion, and its study has created many discussions between different historiographic trends. Answering the question about if Humans were or not sacrificed in Mount Lykaion, literary sources seem to tell that Greeks believed it and, therefore, sacrifices are real. They, sacrifices, are used as a way of building a landscape so as a way of building reality.
Keywords: Human sacrifice; Mount Lykaion; Arcadia